Amino-Thiol Bifunctional Polysilsesquioxane/Carbon Nanotubes Magnetic Composites as Adsorbents for Hg(II) Removal - Xu, Ting; Qu, Rongjun; Zhang, Ying; Sun, Changmei; Wang, Ying; Kong, Xiangyu; Geng, Xue; Ji, Chunnuan (Frontiers in Environmental Chemistry, 2021)
Amino-thiol bifunctional polysilsesquioxane/carbon nanotubes (PSQ/CNTs) magnetic composites were prepared by sol-gel method with two types of functional siloxanes coating on carboxyl CNTs simultaneously. The composites were served as efficient adsorbents for removing Hg(II) in aqueous solution and the adsorption properties were investigated systematically. The optimal pH of bifunctional composites for Hg(II) removal at pH 4.5. The thermodynamic fitting curves are more consistent with the Langmuir model and the adsorption capacities of the bifunctional composites for Hg(II) varied from 1.63 to 1.94 mmol·g-1 at 25 ℃ according to the Langmuir model. The kinetics curves are more fitted to the pseudo-second-order model and the composites could selectively adsorb Hg(II) in a series of binary metal ions solution. The elution regeneration tests showed that the adsorption rate could still reach 78% after repeat cycle three times. It is expected that the bifunctional PSQ/CNTs magnetic composites can be potentially applied to remove low concentration Hg(II) from waste water.